Enhanced-autophagy by exenatide mitigates doxorubicin-induced cardiotoxicity. (1st April 2017) - Lee, Kyung Hye; Cho, Haneul; Lee, Sora; Woo, Jong Shin; Cho, Byung Hyun; Kang, Jung Hee; Jeong, Yun-Mi; Cheng, Xian Wu; Kim, Weon
Abstract: Objectives: Exenatide is a glucagon-like peptide-1 analogue that mitigates myocardial injury caused by ischemia-reperfusion injury via the survival signaling pathway. We hypothesized that exenatide would provide a protective effect in doxorubicin-induced cardiotoxicity. Methods: H9c2 cardiomyocytes were pre-treated with exenatide followed by doxorubicin (DOX), and cell viability and intracellular reactive oxygen species (ROS) were subsequently measured. In order to determine the role of autophagy, we performed western blot as well as TUNEL and autophagosome staining. Additionally, rats were treated with exenatide 1 h prior to every DOX treatment. Left ventricular (LV) function and performance were then assessed by echocardiography. Myocardial and serum ROS was measured with DHE fluorescence and ROS/RNS assay. Results: DOX-induced caspase-3 activation decreased after pre-treatment with exenatide both in vivo and in vitro . Oxidative stress was attenuated by exenatide in H9c2 cells, as well as in cardiac tissue and serum. The number of autophagosomes and autophagic markers were further increased by exenatide in the DOX-treated H9c2 cells, which mediated AMPK activation. Suppression of the autophagosome abolished exenatide-induced anti-apoptotic effect. Echocardiography showed that pre-treatment with exenatide significantly improved LV dysfunction that is induced by DOX treatment. Exenatide inhibits the DOX-induced production of intracellular ROS and apoptosis in the myocardium. The autophagic markers increased in exenatide pre-treated cardiac tissue. Conclusion: Exenatide reduces DOX-induced apoptosis of cardiomyocytes by upregulating autophagy and improving cardiac dysfunction. These novel results highlight the therapeutic potential of exenatide to prevent doxorubicin cardiotoxicity.